Fuzzy Logic: A method to Develop Human like Capabilities for Artificial Intelligence - Jaju, Sangita A; Jagtap, Sudhir B (International Journal of Computer Sciences and Engineering, 2018)
Education of forthcoming century is entirely based on technology. This technology enhances the power and style of learning. This leads to either achieve the desired aim or precede in the learning. The technology based education always offers dynamic adaptation to individual student. However the revolution in learning process has changed the entire traditional concept of learning. E-learning provides a personalized educational environment, which may give complexity in learning and decision making process. Researcher had attempted to focus on this complexity and endeavors to find out more appropriate method for its illustration by taking review of various published research articles. This paper throws light on fuzzy inference system and its mechanism by applying fuzzy logic soft computing tool. Researcher has taken care of measure attribute of fuzzy logic for getting minimal and uncertain data. It also revels prediction in e-learning, empowerment of individual and behavioral learner for making it ease and providing cost benefit to ratio.